IMPROVING STUDENTS’ VOCABULARY MASTERY USING FLASH CARDS - Kartika Ria Utami; Cucu Rahmawati (PROJECT (Professional Journal of English Education), 2019)
This research based paper investigates the students’ vocabulary mastery improvement applying flash cards of which the aims are: (1) finding out whether and to what extent the use of flash cards may improve students' vocabulary and (2) describing the weaknesses and the strengths of implementing flash cards to teach vocabulary. The writer conducted a CAR at the eight grade of a junior high in Cilamaya Kulon, This study was conducted in two cycles  and  conducted  in  four  steps  namely;  planning  the  action,  implementing, observing, and reflecting. The data of the research were collected by using quantitative collection of data techniques. The result of the investigation noticed that Flash cards could improve the students’ mastery of vocabulary. It can be identified from the mean score of the test which increase from 56.5 in the pretest to 77.1 in the posttest one and 83.7 in the posttest two. The use of flash cards may attract the students’ attention to the lesson well. It also might improve participation of students in learning.  They  were  not  shy  anymore  and    really  motivated  to  attend  the instructional process.